2014
DOI: 10.1177/1091581814526891
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Citric Acid, Inorganic Citrate Salts, and Alkyl Citrate Esters as Used in Cosmetics

Abstract: The CIR Expert Panel (Panel) assessed the safety of citric acid, 12 inorganic citrate salts, and 20 alkyl citrate esters as used in cosmetics, concluding that these ingredients are safe in the present practices of use and concentration. Citric acid is reported to function as a pH adjuster, chelating agent, or fragrance ingredient. Some of the salts are also reported to function as chelating agents, and a number of the citrates are reported to function as skin-conditioning agents but other functions are also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…The hydrolysis processes of few simple tri-esters was investigated by Pinnow [541], Pearce and Creamer [542] and Hirata et al [543]. A knowledge about physical properties of citric acid esters is very limited, usually only experimental or predicted boiling points at reduced pressure, sometimes melting points, densities and refraction indices were also reported [493,544]. Citric polyesters are prepared by reactions with 1,2-epoxides (ethylene oxide, propylene oxide, styrene oxide and others), which are catalyzed by small amounts of BF 3 , SnCl 2 or NaOH [494].…”
Section: Esterification and Neutralization Reactions Associated With mentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolysis processes of few simple tri-esters was investigated by Pinnow [541], Pearce and Creamer [542] and Hirata et al [543]. A knowledge about physical properties of citric acid esters is very limited, usually only experimental or predicted boiling points at reduced pressure, sometimes melting points, densities and refraction indices were also reported [493,544]. Citric polyesters are prepared by reactions with 1,2-epoxides (ethylene oxide, propylene oxide, styrene oxide and others), which are catalyzed by small amounts of BF 3 , SnCl 2 or NaOH [494].…”
Section: Esterification and Neutralization Reactions Associated With mentioning
confidence: 99%
“…Various esters or polyesters of citric acid are of large practical importance because organic citrates having numerous applications are usually non-toxic, environment friendly materials [490][491][492][493][494]. Citric acid esters are used as plasticizers in preparation of plastic tubes employed in medical practice, as crosslinkers for starch, cellulose, cotton fabrics and as biodegradable materials used for packing of foods.…”
Section: Esterification and Neutralization Reactions Associated With mentioning
confidence: 99%
“…Acetic acid Safe as used ( 0.0004% in leave-ons; 0.3% in rinse-offs) 4 Ascorbic acid Safe as used ( 10% in leave-ons; 5% in rinse-offs) 5 Benzoic acid Safe as used ( 5% in leave-ons; 5% in rinse-offs; 0.08% in diluted for [bath] use formulations) 6 Benzyl alcohol Safe as used ( 3% in leave-ons; 10% in rinse-offs; 0.9% in diluted for [bath] use formulations) 6 Biotin Safe as used ( 0.6% in leave-ons; 0.01% in rinse-offs) 7 Cholesterol Safe as used ( 5% in leave-ons; 1% in rinse-offs) 8 Citric acid Safe as used ( 4% in leave-ons; 10% in rinse-offs; 39% in diluted for [bath] use formulations) 9 Fumaric acid Safe as used ( 0.2% in leave-ons; 0.2% in rinse-offs; 5% in diluted for [bath] use formulations) 10 Lactic acid Safe for use at 10%, final formulation pH !3.5, when formulated to avoid increasing sun sensitivity or when directions for use include the daily use of sun protection; safe for use in salon products at 30%, final formulation pH !3.0, in products designed for brief, discontinuous use followed by thorough rinsing from the skin, when applied by trained professionals, and when application is accompanied by directions for the daily use of sun protection 11 Malic acid Safe for use as a pH adjuster; insufficient for other uses in cosmetic ingredients 12 Myristic acid Safe as used ( 10% in leave-ons; 19% in rinse-offs) 13 Niacin Safe as used ( 0.1% in leave-ons) 14 Oleic acid Safe as used ( 20% in leave-ons; 19% in rinse-offs) 15,16 Palmitic acid Safe as used ( 16% in leave-ons; 20% in rinse-offs) 15,16 Pantothenic acid Safe as used ( 0.01% in leave-ons: 0.00001% in rinse-offs) 16,17 Salicylic acid Safe as used when formulated to avoid skin irritation and when formulated to avoid increasing the skin's sensitivity to sun, or, when increased sun sensitivity would be expected, directions for use include the daily use of sun protection ( 3% in leave-ons; 3% in rinse-offs) 106 Stearic acid Safe as used ( 22% in leave-ons; 43% in rinse-offs) 15,16 Succinic acid Safe as used ( 0.2% in leave-ons; 26% in rinse-offs) 18 Tocopherol Safe as used ( 2% in leave-ons; 0.4% in rinse-offs; 0.8% in products diluted for use) melatonin in grape skin have ranged from 0.005 to 1.2 ng/g. The stage of growth also affects the amount present.…”
Section: Component Reviewed Conclusion Referencementioning
confidence: 99%
“…Citric acid is a white solid that is soluble in water and some organic solvents [13,14]. It is widely used as a flavor, fragrance, pH adjuster, chelating agent, skin conditioning agent, and buffering agent in foods, beverages, cosmetics, pharmaceuticals, detergents and cleaning products, and pesticides due to its low toxicity [13,14]. According to our analysis, it was used in approximately 6500 personal care and cosmetic products ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It was most commonly found in shampoos (1590 products); body wash, face wash, and exfoliant products (1142 products); conditioners (856 products); moisturizer, cream, lotion, and body oil products (650 products); nail polishes (453); hand washes (261 products); hair dyes (218 products); and foundation, powder, beauty balm, and concealer products (89 products) ( Table 2). The CIR panel reported that citric acid was used at concentrations from 0.0000005 to 10% in cosmetic products, and concluded that citric acid was considered safe in the present practices of use [14]. Citric acid is present in WCD cleansing conditioners at a concentration up to 0.3%.…”
Section: Discussionmentioning
confidence: 99%